PELATIHAN TEKNIK PENGAMBILAN DARAH KAPILER DAN PENGELOLAAN LIMBAH MEDIS PADA PENGURUS KOMISI KESEHATAN GEREJA X [TRAINING OF CAPILLARY BLOOD DRAWING TECHNIQUE AND MEDICAL WASTE MANAGEMENT TO COMMITTEE OF HEALTH COMMISSION IN CHURCH X] - Dora Samaria; Riama Marlyn Sihombing; Theresia Theresia; Maria Maxmilla Yoche (Universitas Pelita Harapan, 2018)
Early detection of degenerative disease can be done by capillary blood screening. Church X Health Commision has a regular working program of blood screening test. However, most of the members of the committee do not have enough knowledge and skills of in performing cappilarry blood drawing technique and managing medical waste. This community service aims to provide information and to train the Health Commission committee in Church X in conducting standard blood tests and managing medical waste. The training methods were lecture, discussion, demonstration and redemonstration to six participants of Health Commission. Participants worked on the pretest questions, were provided training materials, and discussion session. Then, the facilitators supervised the participants to demonstrate blood examination techniques and medical waste disposal practice using digital blood test kits, safety boxes, jerry cans, yellow and black plastic bags. Participants practiced the activities three to five times. At the end of the training, participants filled out the posttest questionnaire. Paired t Test results showed that the mean pretest score was 47.92, while the mean posttest score was 83.33 (p value 0.005). It was concluded that there was a significant difference between the average knowledge scores of the participants before and after the training. It is hoped that the Health Commission Committee can apply the knowledge and skills that have been acquired in this service.